Potential of Epigallocatechin-3-Gallate and 5-Fluorouracil Combination in Colorectal Cancer Therapy: Literature Review - Syalsabila, Dara Pitra; Manafe, Carolina Janicca Winda (Jurnal Biologi Tropis, 2024)
This article reviews the potential of combining Epigallocatechin-3-Gallate (EGCG) from green tea and 5-Fluorouracil (5-Fu) to enhance the effectiveness of colorectal cancer therapy. Colorectal cancer is a common type of cancer with a high mortality rate, particularly due to resistance to standard therapies like 5-Fu. The article aims to explore the potential of EGCG as a combination therapy to overcome resistance and reduce the side effects of chemotherapy. The method used is a narrative literature review, collecting studies from PubMed, google scholar and proquest databases. The review findings show that EGCG can induce apoptosis, inhibit cancer cell growth, and increase cell sensitivity to 5-Fu. The combination of EGCG and 5-Fu has proven effective in suppressing cancer cell proliferation and reducing resistance to 5-Fu, especially in drug-resistant colorectal cancer cells. In conclusion, the EGCG and 5-Fu combination has the potential to become a more effective and safer colorectal cancer therapy with a lower risk of side effects, offering a promising prospect for future cancer therapy development.